POSTURAL REGULATION OF PATIENTS IN THE ACUTE PERIOD OF ISCHEMIC STROKE ACCORDING TO STABILOMETER DATA - Нина Геннадьевна Коновалова; Ирина Николаевна Шарапова; Лариса Геннадьевна Горохова; Нелли Ивановна Ромашевская; Лариса Николаевна Макарова (Медицина в Кузбассе)
13 patients in the acute period of ischemic stroke where examined.